Innate immune response of host cells infected with Salmonella - Fan Hongfei; Lu Juane; Wu Hao; Ruan Haihua; Song Wenjun (BIO Web of Conferences, 2024)
Salmonella is one of the most common pathogenic bacteria with a wide range of hosts and can be transmitted by various routes, infecting animals and humans and causing a range of gastrointestinal and systemic diseases. The innate immune system acts as the frontline defense against pathogenic bacteria, triggering inflammatory and antimicrobial responses by coordinating multiple signaling pathways through host pattern recognition receptors. The success of Salmonella infection is largely dependent on the host’s innate immune defense. This article reviews the process of Salmonella infection and the innate immune defense response of host cells infected with Salmonella.